2018
DOI: 10.1111/pde.13422
|View full text |Cite
|
Sign up to set email alerts
|

Use of topical therapies for pediatric psoriasis: A systematic review

Abstract: Psoriasis is one of the most common chronic skin diseases, affecting 1%-3% of the general population. It can have a significant negative impact on a patient's quality of life, and in approximately 30% of patients first symptoms can be traced back to childhood. We have performed a comprehensive literature search using the MEDLINE database in order to ascertain the efficacy and adverse reactions of topical treatments in pediatric psoriasis. A total of 13 relevant articles were identified on the following topical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The use of TCS on certain body areas that have thin skin, such as the face, folds, and genital areas, is limited by their risk of skin atrophy, telangiectasia, and striae. 12,13 There is high-quality evidence supporting the efficacy and tolerability of TCIs applied to plaque psoriasis of the face and intertriginous and genital areas in pediatric 49,50 and adult patients, 51 -54 and their use on these areas is supported by treatment guidelines. 55 -57…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of TCS on certain body areas that have thin skin, such as the face, folds, and genital areas, is limited by their risk of skin atrophy, telangiectasia, and striae. 12,13 There is high-quality evidence supporting the efficacy and tolerability of TCIs applied to plaque psoriasis of the face and intertriginous and genital areas in pediatric 49,50 and adult patients, 51 -54 and their use on these areas is supported by treatment guidelines. 55 -57…”
Section: Resultsmentioning
confidence: 99%
“…The use of TCS on certain body areas that have thin skin, such as the face, folds, and genital areas, is limited by their risk of skin atrophy, telangiectasia, and striae. 12,13 There is high-quality evidence supporting the efficacy and tolerability of TCIs applied to plaque psoriasis of the face and intertriginous and genital areas in pediatric 49,50 and adult patients, [51][52][53][54] and their use on these areas is supported by treatment guidelines. [55][56][57] There is also evidence from meta-analyses 58,59 and double-blind RCTs 60,61 supporting the use of TCIs for the treatment of genital lichen sclerosus, although TCIs have generally been found to be less effective than TCS in comparative trials.…”
Section: Off-label Use Of Tcis That Is Well Supported By the Literaturementioning
confidence: 99%
“…The pathogenesis of psoriasis is complex, with both genetic and environmental factors. 80 Real-time reverse transcription PCR analysis showed that psoriasis-associated nonprotein coding RNA induced by stress (PRINS), a novel psoriasis susceptibility-related lncRNA gene, is expressed at higher levels in the uninvolved epidermis of psoriatic patients compared with the level in both psoriatic lesioned tissue and healthy epidermal tissue, suggesting a role for PRINS in psoriasis susceptibility. 13,81 G1P3 (also named IFI6, interferon alpha inducible protein 6) inhibits spontaneous keratinocyte apoptosis, and its high expression in psoriatic skin may thus contribute to the development of psoriatic lesions.…”
Section: Lncrnas and Human Autoimmune Diseasesmentioning
confidence: 99%
“…Psoriasis is a common chronic inflammatory disease characterized by abnormal keratinocyte proliferation. The pathogenesis of psoriasis is complex, with both genetic and environmental factors …”
Section: Introduction Of Lncrnasmentioning
confidence: 99%
“…However, the high cost and increased risk of infection associated with the systemic delivery of these drugs restricts their use to moderate-to-severe cases of psoriasis. For milder forms of psoriasis (more than 80% of patients), topical corticosteroids remain the predominant option (Greb et al, 2016;Kravvas and Gholam, 2018). Monoclonal antibodies are unable to penetrate the psoriatic epidermis for topical use, and topical approaches using small molecule inhibitors have not advanced for psoriasis.…”
Section: Introductionmentioning
confidence: 99%